EDUKASI THOHAROH DALAM BUKU CATATAN DAILY HAID - Nazriyah Nazriyah; Siti Asiah; Suprihatin Suprihatin; Akmal Rizki Gunawan Hasibuan (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
The lack of knowledge about the boundaries of blood and purity is acknowledged to occur in every village that has minimal knowledge of fiqh. Knowing the foundation in the law of women's fiqh can be one of the changes in how to pay attention to menstruation with worship which is the purpose of human life created. There are many hidden intentions in participating in specific learning that is carried out with taklim majlis or health seminars. Potentially in the community, there are majlis taklim women or Balligh youth who are gathered at TPA Darur Rahmah. This religious learning uses the lecture method with 1 community leader reading a book "Addardir Isra' Wal Mi'raj" and the enthusiasm for gathering to recite the Koran is very high. Sindangsari Village, which coincides in Kampung Putat Rt 003 Rw 002, has a fairly busy recitation schedule for both children and housewives. With this potential, the program to introduce the matter of thoharoh and the chapter on menstruation can be delivered specifically using the book "Daily Haid notes".